PEMAKNAAN MAHASISWA TERHADAP SIMBOL PANCASILA SEBAGAI IDENTITAS BANGSA - Nerrisa Erviana Hadianti Kustoyo; Siti Zunariyah (Journal of Development and Social Change, 2019)
The purpose of this study is to: To find out the meaning of the Pancasila symbol in the souls of students, To find out the practice of Pancasila values on student life, To know students in responding to Pancasila towards the meaning of a nation's identity.This study uses qualitative methods through in-depth interview techniques, and direct observation. Primary data obtained from interviews. The sampling of this study was through purposive sampling.The results of this study are:  The meaning of students towards Pancasila based on Max Weber's theory of action can be categorized into rational values (werk rational) which are based on divine values, mutual respect, adab, and humanity, and the value of justice. Besides affective actions based on the love of water and unity, The application of Pancasila into the daily lives of students can be categorized into rational acts of values based on mutual respect and do not differentiate between religious adherents, values unity and value of deliberation to reach consensus; affective actions based on the love of the motherland; instrumental rational actions based on means of respect and tolerance to achieve peace and unity, and means of association, participation in activities in society, Student attitudes towards Pancasila as a nation's identification are categorized into rational acts of value based on values respect for differences, values of togetherness or unity; instrumental rational value actions (zwerk rational) which are based on means of deliberation to reach consensus, the struggle to achieve goals; Affective action that is based on the love of the motherland.